Children, Families and Schools - Beveridge Sally; Routledgefalmer (2005)
This book offers a clear and coherent overview of a complex topic, ensuring its appeal to students and practitioners alike. Acknowledgements, Introduction, Developing Policy Frameworks, Home and Family: Contexts for Learning, Educational Disadvantage and the Home-School Relationship, Developing Home - School Relationships, Children's Participation in the Home - School Relationship, Towards Partnership and Participation, References, Index.